Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13063-020-04913-y
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: BCG revaccination of health workers in Brazil to improve innate immune responses against COVID-19: A structured summary of a study protocol for a randomised controlled trial

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…It is suggested that induction of the innate immunity by Bacillus Calmette-Guerin (BCG) vaccination or previous infections could lead to protection against other (intracellular) pathogens [16,17]. BCG vaccination already showed protection against respiratory tract infections in elderly patients [18][19][20] and trials assessing the protection of BCG vaccination against SARS-CoV-2 are currently conducted [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that induction of the innate immunity by Bacillus Calmette-Guerin (BCG) vaccination or previous infections could lead to protection against other (intracellular) pathogens [16,17]. BCG vaccination already showed protection against respiratory tract infections in elderly patients [18][19][20] and trials assessing the protection of BCG vaccination against SARS-CoV-2 are currently conducted [21][22][23].…”
Section: Introductionmentioning
confidence: 99%